A Sociological Study of the Health Problems of the Rural Area of Dera Ghazi Khan - Khan, Saad Ahmed (Al Khadim Research Journal of Islamic Culture and Civilization, 2025)
It takes on a more serious form in developing countries like Pakistan, where democratic and administrative institutions are weak and societies are politically unstable, and where public health is not one of the top priorities of governments. Scientific research and statistics indicate that the growing population is reducing the resources available for public health, especially during childbirth, which severely affects the infrastructure of women and children. The people of rural areas live very close to the nature but also confront important challenges. These problems include lack of human service medical professional and facilities. On the other side, rural areas are often poor and lack the basic services, employment opportunities. Rural areas often lack sufficient numbers of health care professionals, hospitals, and basic health centres. Problem is the long distances that ambulances and patients must travel. Because ambulances and other emergency vehicles must travel so far, rural residents with any emergencies receive medical attention more slowly than their urban counterparts. The long distance that people must travel makes it more difficult for patients with health problems to receive medical care. Any case of medical emergency that needs to be treated within 2-3 hours might have to travel equal or more hours in each direction to receive treatment. Travel distances in rural areas also mean that rural residents are less likely than urban residents to receive preventive services. It was concluded that availability of emergency services were associated with patients satisfied with provided Basic Health Unit services. Medical facilities were associated with patients satisfied with provided medical facilities in Basic Health Unit. Doctor check-up was linked with patient’s satisfaction with doctor’s availability. Doctor’s availability was associated with beneficial for rural people during emergency. Patient’s satisfaction with paramedical staff performance in rural area. The study focuses a small region Dera Ghazi Khan for its health issues especially in the rural areas where insufficent facilities are the real challenges for health.